2023
DOI: 10.1088/2050-6120/acfb58
|View full text |Cite
|
Sign up to set email alerts
|

A new twist on PIFE: photoisomerisation-related fluorescence enhancement

Evelyn Ploetz,
Benjamin Ambrose,
Anders Barth
et al.

Abstract: PIFE was first used as an acronym for protein-induced fluorescence enhancement, which refers to the increase in fluorescence observed upon the interaction of a fluorophore, such as a cyanine, with a protein. This fluorescence enhancement is due to changes in the rate of cis/trans photoisomerisation. It is clear now that this mechanism is generally applicable to interactions with any biomolecule and, in this review, we propose that PIFE is thereby renamed according to its fundamental working principle as photoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 163 publications
0
2
0
Order By: Relevance
“…This leads to a remarkable 70-fold increase in fluorescence intensity under optimal conditions and enables the detection of glucose in serum samples, demonstrating a low limit of detection (10 μM) and a linear response within the concentration range of 50 μM to 2000 μM. Protein-induced fluorescence enhancement is a powerful method that significantly enhances fluorescence intensity when a protein binds closely, allowing for high-resolution studies of molecular interactions without the need for protein labeling [ 222 , 223 , 224 ].…”
Section: Methods For Fluorescence Enhancementmentioning
confidence: 99%
“…This leads to a remarkable 70-fold increase in fluorescence intensity under optimal conditions and enables the detection of glucose in serum samples, demonstrating a low limit of detection (10 μM) and a linear response within the concentration range of 50 μM to 2000 μM. Protein-induced fluorescence enhancement is a powerful method that significantly enhances fluorescence intensity when a protein binds closely, allowing for high-resolution studies of molecular interactions without the need for protein labeling [ 222 , 223 , 224 ].…”
Section: Methods For Fluorescence Enhancementmentioning
confidence: 99%
“…S1E, F, Table 1). Due to the innate environmental sensitivity of cyanine dyes [20,21], we explored whether PEPCy tags modified the fluorescence lifetimes of their cognate dyes. Fluorescence lifetime microscopy (FLIM) of PEPCy expressing yeast cells showed that both PEPCy3 and PEPCy5 increased the lifetime of their cognate cyanine dyes compared to covalent targeting of the dyes via HT (Fig.…”
Section: Mainmentioning
confidence: 99%